Examining The Foundations Of Academic Books: A Longmanian Analysis Of The Oxford Eap Elementary/A2 Student Book - Abdul Syahid; Weni Wulandari; Alya Audria; Mirna Lestari; Siti Rahmawati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This article delves into the analysis of the Oxford EAP Elementary/A2 Student Book using the analytical framework developed by M.H. Longman. The focus lies on comprehending the structure, content, and learning objectives embedded within the textbook. Through the Longmanian framework, various aspects such as clarity, consistency, relevance to learning objectives, variation in material presentation, and student engagement are evaluated. The analysis aims to provide insights into how the book is designed and utilized in educational contexts, thereby enhancing its effectiveness in supporting student learning at the Elementary/A2 level in academic language contexts. Additionally, the integration of language skills and academic skills within the book is explored to assess its role in preparing students for success in English-speaking academic environments at university level.